Paratekst w służbie propagandy. Wprowadzenia w przekładach literatury pięknej na język polski i czeski w latach 50. XX wieku - Królak, Joanna (Przekłady Literatur Słowiańskich, 2017)
Paratext Serving Propaganda in the Introductions to Literary Translations to Polish and Czech in the 1950’s The article describes the role of propaganda and aims of the introductions to Polish and Czech literary translations in the 1950’s. It discusses the influence of the contemporary cultural politics on the selection of literary works that were translation-worthy, and that were provided with mandatory introduction. The article presents the dominant strategies of biographical and literary manipulation in the works of such writers as Bozena Nemcova, Jan Neruda, Alojs Jirasek and Adam Mickiewicz. Keywords: cultural politics, realism, Romanticism, paratext, propaganda